Imagining the Future: Young Australians on sex, love and community - Bulbeck, Chilla (University of Adelaide Press, 2012)
Do young Australians understand and live 'equality' and 'difference' differently from older generations? Is Australia the gender equal society that many claim it to be? How do we understand and explain growing economic inequality when our dominant ideologies are individualism and neoliberalism? What are or should be the limits of tolerance in our negotiation of cultural difference? Imagining the Future explores our contemporary complex equality narrative through the desires and dreams of 1000 young Australians and 230 of their parents from diverse backgrounds across Australia. This 'extraordinary' data set affords analysis of the impact of gender, socio-economic disadvantage, ethnicity, Aboriginality and sexuality on young people's 'imagined life stories', or essays written about their future. An intergenerational comparison assesses how different young people really are from older generations. The book offers a compelling and subtle engagement with the sometimes 'deeply moving', sometimes 'hilarious' voices of young people to deliver insight into the challenges and complexity of gender and other social relations in early 21st Australian society.